Modeling of Turbulent Flow around Bubbles in Molten Steel. Issue 6 (16th April 2019) - Duan, Haojian; Ren, Yin; Zhang, Lifeng
Abstract : Turbulent flow around bubbles in the molten steel is predicted by using a two‐dimensional axisymmetric model. The dependence of bubble terminal velocity and bubble shape on its size is taken into account. The recirculation region is not observed for the free spherical and spheroidal bubbles, while it is found at the rear of the free spherical‐cap bubbles and the rigid bubbles. For the free spherical and spheroidal bubbles, the velocities at the rear of bubbles and at the bubble surface are raised with increasing turbulence kinetic energy. For free spherical‐cap bubbles and rigid bubbles, the wake flow is more easily formed in the weaker turbulence and the recirculation volume increases as the turbulent kinetic energy decreases. Abstract : Turbulent flow around bubbles in the molten steel is predicted as a function of the global turbulent kinetic energy. The dependence of bubble terminal velocity and bubble shape on its size is taken into account. The recirculation region at the rear of bubbles with different shapes is discussed and the flow fields around rigid bubbles and free bubbles are compared.